1986
DOI: 10.1016/0095-8956(86)90064-x
|View full text |Cite
|
Sign up to set email alerts
|

An integer analogue of Carathéodory's theorem

Abstract: We prove a theorem on Hilbert bases analogous to Caratheodory's theorem for convex cones. The result is used to give an upper bound on the number of nonzero variables needed in optimal solutions to integer programs associated with totally dual integral systems. For integer programs arising from perfect graphs the general bounds are improved to show that if G is a perfect graph with n nodes and ''" is a vector of integral node weights, then there exists a minimum 11•-covering of the nodes that uses at most n di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 15 publications
1
68
0
Order By: Relevance
“…Then |a T x i − a T x j | ≤ 1 for any i and j, since otherwise we can replace x i and x j by λx i + (1 − λ)x j and λx j +(1−λ)x i , where λ = 1/|a T x i −a T x j | thus reducing (6). Hence a T x i ∈ {q, q +1} for each i = 1, .…”
Section: Integer Decompositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then |a T x i − a T x j | ≤ 1 for any i and j, since otherwise we can replace x i and x j by λx i + (1 − λ)x j and λx j +(1−λ)x i , where λ = 1/|a T x i −a T x j | thus reducing (6). Hence a T x i ∈ {q, q +1} for each i = 1, .…”
Section: Integer Decompositionmentioning
confidence: 99%
“…With a little more care (as was pointed out by an anonymous referee), a decomposition can be found in polynomial time as follows (see [6,8]). First, t ≤ n + 1 affinely independent integer vectors y 1 , .…”
Section: Integer Decompositionmentioning
confidence: 99%
“…All essential ingredients except unimodularity are already included in the proof of Fulkerson's pluperfect graph theorem [17]. Fulkerson's proof suggests a greedy way of taking active rows with an integer coefficient (see below); this is often exploited to prove that some particular systems are TDI, let us only cite two papers the closest to ours, Cook, Fonlupt & Schrijver [6] and Chandrasekaran & Tamir [3]. The latter paper extensively used lexicographically best solutions, which is an important tool in linear programming theory.…”
Section: Is Equivalent To: the Matrix A Defining A Set Packing Polytomentioning
confidence: 99%
“…More precisely, the main result of Section 3 is the following: The proof relies on the basic idea of Fulkerson's famous "pluperfect graph theorem" [17] stating that the integrality of such polyhedra implies their total dual integrality in a very simple "greedy" way. Chandrasekaran and Tamir [3] and Cook, Fonlupt and Schrijver [6] exploited Fulkerson's method by pointing out its lexicographic or advantageous Carathéodory feature. In [35, §4] it is noticed with the same method that the active rows of the dual of integral set packing polyhedra (the cells of their normal fan) have a unimodular subdivision, which can be rephrased as follows: the normal fan of integral set packing polyhedra has a unimodular refinement.…”
Section: Introductionmentioning
confidence: 99%
“…A finite set of vectors X is called a Hilbert basis, if each integer vector b ∈ cone(X) is a nonnegative integer combination of elements in X. Cook, Fonlupt and Schrijver [2] provided the following integer analogue of Carathéodory's theorem: If cone(X) is pointed and if X ⊆ Z d is an integral Hilbert basis, then for every b ∈ cone(X) there exists a subset X ⊆ X with | X| ≤ 2 d − 1 such that b is an integer conic combination of vectors in X. Sebő [8] improved this bound to 2 d − 2. Bruns et al [1] have shown that the bound d is not valid.…”
Section: Related Workmentioning
confidence: 99%